ANALISIS SISTEM INFORMASI AKUNTANSI PENJUALAN KREDIT PADA PT. RAJAWALI TANJUNGSARI ENJINIRING - Fatma Rizki Fauria; Varid Martah (Jurnal Nirta : Inovasi Multidisiplin, 2025)
This research was conducted at PT. Rajawali Tanjungsari Enjiniring, the purpose of this research is to determine whether the credit sales accounting information system has been running effectively and efficiently. The research method used is a descriptive method. While the benefits of this research are as a consideration and input related to the credit sales procedure at PT. Rajawali Tanjungsari Enjiniring to be better. In this study, the author uses primary data and secondary data such as interview results, observations and documentation as well as data on credit sales at PT. Rajawali Tanjungsari Enjiniring. An accounting system is a series of forms, records and reports that are arranged in a certain way to provide financial information needed by management and play an important role in making company decisions. The results of the study indicate that the credit sales accounting system at PT. Rajawali Tanjungsari Enjiniring has implemented a good accounting recording system and is in accordance with applicable accounting principles.